Harvesting Cooling Effect on LPG-Fueled Vehicles for Mini Cooler: A Lab-Scale Investigation - Setiyo, Muji; Widodo, Noto; Purnomo, Bagiyo Condro; Munahar, Suroto; Rahmawan, Muhammad Andi; Luthfi, Akbar (Indonesian Journal of Science and Technology, 2019)
This article presents an investigation of the actual cooling effect on a lab-scale prototype of LPG-fueled vehicles. The cooling effect is obtained from heat absorption by LPG on the vaporizer. Water with a mass flow rate of 1, 2 and 3 lpm is flowed from the cooling box to the LPG evaporator and flow back to the cooling box. The car used in this study has a capacity of 1500 cc that rotates 1000, 1500, and 2000 rpm. The results showed that there was a relationship between cooling power with the increase in engine speed and mass flow rate of water that crosses the evaporator. The biggest cooling power is 378 Watts at 1000 rpm with a water mass flow rate of 3 lpm.